Solid magnetoliposomes entrapping new potential antitumor drugs for applications in cancer therapy - Ferreira, João M. C. (2019)
In this work, new solid magnetoliposomes (nanoparticle aggregates covered by a lipid/surfactant bilayer), containing manganese ferrite nanoparticles, have been developed. For that, a first layer of octadecylamine (ODA) was covalently linked to the nanoparticles surface and then covered by a layer of the phospholipid DPPC (second layer). These nanosystems exhibit diameters below 150 nm and the capability to interact with models of biomembranes (Giant Unilamellar Vesicles, GUVs) by fusion. The solid magnetoliposomes were successfully tested as nanocarriers for new fluorescent promising antitumor compounds.